FAM111B Overexpression and Immune Cell Infiltration: Implications for Ovarian Cancer Immunotherapy - Wanying Li; Fang Wei; Ting Zhou; Lijuan Feng; Lihong Zhang (Biomedicines, 2025)
Background: Ovarian cancer (OC) is characterized by high incidence and mortality rates; however, due to its immunologically “cold” phenotype, the effectiveness of immunotherapy as a strategy for OC remains inadequate. Although the FAM111B gene promotes the progression of various solid tumors, its specific function within the tumor immune microenvironment (TIME) of OC remains unclear. Methods: This study used multiplex immunofluorescence techniques and bioinformatics analysis to examine the role of FAM111B within the TIME of OC. Through multiplex immunofluorescence, we assessed the protein expression levels of FAM111B alongside key immune cell markers, including FOXP3, CD4, CD8, CD68, CD163, CD66b, and CD11c. Furthermore, we employed bioinformatics methods using The Cancer Genome Atlas database to validate FAM111B function at the mRNA level in OC. Results: We observed a positive correlation between FAM111B expression and immune cell infiltration, including T cells, macrophages, and dendritic cells. FAM111B, M2 macrophages, and regulatory T cells were associated with poorer overall survival in OC patients. Additionally, specific T cell subsets and dendritic cells were correlated positively with programmed death-ligand 1 expression, while FAM111B levels were linked to multiple immune checkpoint molecules. Conclusions: This study reveals a positive correlation between FAM111B overexpression and the infiltration levels of immune cells in OC. In OC patients characterized by elevated FAM111B expression, the potential augmentation of immune cell infiltration within the TIME may consequently enhance the efficacy of immunotherapy.